Transgenic Plants That Express the Phytoplasma Effector SAP11 Show Altered Phosphate Starvation and Defense Responses. Issue 3 (24th January 2014) - Lu, Yen-Ting; Li, Meng-Ying; Cheng, Kai-Tan; Tan, Choon Meng; Su, Li-Wen; Lin, Wei-Yi; Shih, Hsien-Tzung; Chiou, Tzyy-Jen; Yang, Jun-Yi
Abstract : Expression of a bacterial effector alters plant responses to phosphorus nutrient and a bacterial pathogen . Abstract: Phytoplasmas have the smallest genome among bacteria and lack many essential genes required for biosynthetic and metabolic functions, making them unculturable, phloem-limited plant pathogens. In this study, we observed that transgenic Arabidopsis ( Arabidopsis thaliana ) expressing the secreted Aster Yellows phytoplasma strain Witches' Broom protein11 shows an altered root architecture, similarly to the disease symptoms of phytoplasma-infected plants, by forming hairy roots. This morphological change is paralleled by an accumulation of cellular phosphate (Pi ) and an increase in the expression levels of Pi starvation-induced genes and microRNAs. In addition to the Pi starvation responses, we found that secreted Aster Yellows phytoplasma strain Witches' Broom protein11 suppresses salicylic acid-mediated defense responses and enhances the growth of a bacterial pathogen. These results contribute to an improved understanding of the role of phytoplasma effector SAP11 and provide new insights for understanding the molecular basis of plant-pathogen interactions.